2018
DOI: 10.1093/ajh/hpy038
|View full text |Cite
|
Sign up to set email alerts
|

West African Ancestry and Nocturnal Blood Pressure in African Americans: The Jackson Heart Study

Abstract: West African ancestry was not associated with nocturnal hypertension and nondipping blood pressure among African Americans. While rare genetic variants cannot be ruled out, these data highlight the need to better understand how environmental and behavioral factors contribute to differences in nocturnal blood pressure among African Americans compared with European Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Finally, in line with studies in adults, we also identified that Black race was significantly associated with blunted nocturnal dipping in children with glomerular CKD (36,37). Further studies in children are needed to determine whether these racial differences are related to environmental factors, diet, genetic differences, or a combination of these (38).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in line with studies in adults, we also identified that Black race was significantly associated with blunted nocturnal dipping in children with glomerular CKD (36,37). Further studies in children are needed to determine whether these racial differences are related to environmental factors, diet, genetic differences, or a combination of these (38).…”
Section: Discussionmentioning
confidence: 99%
“…When adopting a social sciences theory of health disparities, scientists estimating causal effects of genetic ancestry on health outcomes should control for variables assumed to be consequences of historical systematic racism, discrimination, and segregation to avoid conflating genetic ancestry effects with these other correlates of SIRE. A growing number of multilevel studies have examined African ancestry as a predictor of chronic disease endpoints [20,21,36,46,[63][64][65][66][67]. Geographic analyses of migration patterns in the US have shown that genetic admixture patterns in present-day African Americans are associated with forced movements of people that occurred during the trans-Atlantic slave trade [23,24].…”
Section: Plos Onementioning
confidence: 99%
“…Disentangling the contributions of genetic, societal, and environmental factors toward disparities in hypertension has important clinical and public health implications for improving care and reducing the morbidity and mortality attributed to hypertension among Black individuals . Hypertension affects nearly 1 in 2 Black adults, who additionally experience higher rates of severe, nocturnal, and nondipping phenotypes, as well as reduced responsiveness to standard BP regimens, contributing to notions of an innate biological risk associated with Black race . In SPRINT, prior studies reported racial differences in the risk of adverse outcomes and the number of antihypertensive medications required to reach the intensive SBP goal.…”
Section: Discussionmentioning
confidence: 99%